EKSISTENSI PARTAI POLITIK DAN PEMILU LANGSUNG DALAM KONTEKS DEMOKRASI DI INDONESIA - Artis Artis (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
General election constitutes medium in channel society aspiration on democratic state via political party. Year general election 2004 followed by a lot of executed political party straightforward and democracy corresponds to section 6A about president and vice president elect and section 18 sentence 4 UUD 1945 about region head elects democratically.